KECENDERUNGAN PERILAKU BERWIRAUSAHA WARGA BELAJAR TERHADAP PELATIHAN SABLON DI PKBM CAHAYA ILMU KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - S, Fredrico M; Maemunaty, Titi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by several phenomena that occur in theenvironment PKBM Light Sciences and based on the results of previous observations,which are both associated with a trend towards behavioral entrepreneurship trainingresidents to learn screen printing. Therefore the aim of this study was to determine thebehavior tendencies of entrepreneurship learners to the training of screen printing inPKBM Cahaya Ilmu Kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaru. Thisresearch is a descriptive qualitative approach. This research was conducted at PKBMCahaya Ilmu Kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaru. Subjects ofthis study consisted of five persons, namely 2 a key informant who is a national study,two people to become informants who are citizens studying control and one informantobserver are tutor. Data were collected by observation, interview and documentation.The research data that has been analyzed by the data analysis technique based on theopinion of Miles and Huberman, namely data reduction, data model and conclusion.Based on the research method is run, it is the conclusion of this study is the Personalityresidents learned that is well established, the demonstrated high initiative in learningstudied. Citizen have a good relationship and to establish good communication alsowith fellow learners and tutors. Residents learned already can prepare marketingstrategies printing results that are ready to be traded in the market screening. Citizenlearning can organize activities screening become an entrepreneurial interest in themarket. But people do not learn they are better equipped to manage an entrepreneurialscreening. Residents learn yet have adequate capital and yet they are better equipped tomanage the finances.Keywords: trend, entrepreneurial behavior, screen printing training.